1985
DOI: 10.1111/j.1365-2842.1985.tb00640.x
|View full text |Cite
|
Sign up to set email alerts
|

The effective minimum cement thickness of zinc phosphate cement for luted non‐precious crowns

Abstract: Non-precious metal crowns were prepared for natural teeth which were ground to a taper angle of 5 degrees. The movement of the crowns on teeth during repeated try-on seating was measured with a micrometer. Increasing the applied load from 2 to 10 kg resulted in an average crown movement of 63 micron. For most samples this movement continued when try-on was repeated. Casting irregularities were found to create furrows on some regions of the axial tooth surface during try-on seating. The diameter of the ADA spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
2

Year Published

1988
1988
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 13 publications
0
19
0
2
Order By: Relevance
“…This phenomenon has been described as 'uncemented grip' or 'frictional fit' and is a known limiting factor in crown seating 29 but its role in retaining the cast restoration has only been investigated to a limited degree.…”
Section: Die-spacing and Crown Retention A) Pre-cementation Retentionmentioning
confidence: 99%
See 3 more Smart Citations
“…This phenomenon has been described as 'uncemented grip' or 'frictional fit' and is a known limiting factor in crown seating 29 but its role in retaining the cast restoration has only been investigated to a limited degree.…”
Section: Die-spacing and Crown Retention A) Pre-cementation Retentionmentioning
confidence: 99%
“…Increased convergence angle also favo u r e d decreased crown elevation in the study of Eames et al 2 Studies have further demonstrated variations in the seating of cast restorations due to the various materials and techniques involved in the impression, die construction and casting procedures. Grajower et al 29 have demonstrated the variability in cement film thickness produced with changes in the powder:liquid ratio and ambient temperature for zinc phosphate cement. A delay in seating following mixing of the cement also has been shown to result in increased seating discrepancies.…”
Section: Die-spacing and Crown Seatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Os dados obtidos (µm) foram submetidos à análise estatística (ANOVA) e teste de Tukey (p<0.05). Para a condição material, a liga VB (118,73) não apresentou diferença estatisticamente significante em relação à liga VB II (93,40), sendo que estas apresentaram diferença estatisticamente significante em relação ao 35). Em relação ao fator espaçador, houve diferença estatisticamente significante entre as três condições (G0=177,31; G1=121,51 e G2=81,66).…”
unclassified